Subclinical depressive symptoms during pregnancy and birth outcome - a pilot study in a healthy German sample - Wallwiener, Stephanie; Waldeier, Lena Marie; Müller, Mitho; Szabo, Akos; Sohn, Christof; Reck, Corinna (Archives of women's mental health, 2013)
There is a high prevalence of depression in Germany and all over the world. Maternal depressive symptoms during pregnancy have been shown in some studies to be associated with an increased risk of preterm birth and low birth weight. The influence of maternal depressive symptoms during pregnancy on preterm delivery and fetal birth weight was investigated in a prospective single-centre study. A sample of 273 healthy pregnant women was assessed for symptoms of antepartum depression. Symptoms were measured using the Edinburgh Postnatal Depression Scale (EPDS) and the Patient Health Questionnaire (PHQ). Symptoms of anxiety were assessed using the State/Trait Anxiety Inventory. Patients who scored above the cutoff were contacted by phone for a Structured Clinical Diagnostic interview. Neonatal measurements were obtained from the birth registry of the Department of Obstetrics. Baseline data were assessed with a self-styled data sheet. Prevalence of elevated depressive symptoms was 13.2 % when measured with the EPDS and 8.4 % with the PHQ. According to DSM-IV criteria, only four (EPDS) respective two (PHQ-D) of these patients could be diagnosed with a depressive disorder and ten (EPDS) respective seven (PHQ) with an anxiety disorder. There was no significant influence on preterm birth or birth weight. Maternal depressive symptoms are self-reported. Elevated subclinical symptoms of depression and anxiety during pregnancy are common. However, this study showed no evidence that these symptoms are associated with adverse pregnancy outcome.